FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BEI 2015-2021 (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2023)
This study aims to determine the effect of several financial ratios on the performance of telecommunications infrastructure provider companies focused on telecommunications tower infrastructure provider companies at PT Sarana Menara Nusantara Tbk, PT Tower Bersama Infrastruktur Tbk, PT Solusi Tunas Pratama Tbk, PT Centratama Telekomunikasi Indonesia Tbk and PT Bali Towerindo Sentra for the 2015 - 2021 period taking into account the current ratio (CR), debt to equity ratio (DER) and return on asset ratio (ROA). The method used in this research is descriptive method with quantitative approach. The data analysis technique in this study uses the Tobin's Q value ratio. The results show that the variable current ratio (CR), debt to equity ratio (DER) and return on asset ratio (ROA) together have significant effect on company performance of Tobin's Q for telecommunications companies, the current ratio (CR) variable has negative effect but not significant on the company performance of the Tobin's Q proxy, then the debt to equity ratio (DER) variable has positive effect but not significant on the Tobin's Q proxy company performance, and finally the return on assets (ROA) has positive and significant effect on the company performance of the Tobin's Q proxy for telecommunications tower provider companies.